2008
DOI: 10.1007/s00428-008-0703-9
|View full text |Cite
|
Sign up to set email alerts
|

One-step nucleic acid amplification—a molecular method for the detection of lymph node metastases in breast cancer patients; results of the German study group

Abstract: Sentinel lymph node (SN) biopsy is part of the staging procedure in breast cancer patients. In this study, we compared an intraoperative tool named one-step nucleic acid amplification (OSNA) to our routine histological investigation. OSNA consists of a short homogenization step followed by amplification of cytokeratin (CK) 19 mRNA directly from the lysate. To evaluate the performance of OSNA in comparison to histology, analysis of 343 axillary lymph nodes (ALN) from 93 breast cancer patients was performed with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
69
1
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 100 publications
(80 citation statements)
references
References 28 publications
6
69
1
4
Order By: Relevance
“…The study by Schem et al 60 reported a sensitivity of 98.1% and a specificity of 91.7% for OSNA compared with five-level histopathology. After adjustment for TAB, sensitivity increased to 100% and specificity to 96.5%.…”
Section: Single-gate Studiesmentioning
confidence: 99%
See 4 more Smart Citations
“…The study by Schem et al 60 reported a sensitivity of 98.1% and a specificity of 91.7% for OSNA compared with five-level histopathology. After adjustment for TAB, sensitivity increased to 100% and specificity to 96.5%.…”
Section: Single-gate Studiesmentioning
confidence: 99%
“…The study reported by Schem et al 60 provides minimal information on patient characteristics or recruitment. Five-level histology was used as the reference standard and the outcome assessors were blinded.…”
Section: Metasinmentioning
confidence: 99%
See 3 more Smart Citations